Triglycerides and Acne: Assessing the Impact of Blood Lipid Levels on Acne Severity in Young Adults - Wardani, Erika Martining; Nugroho, Riezky Faisal (Utan Kayu Publishing, 2024)
Acne vulgaris is a common chronic inflammatory skin condition that predominantly affects adolescents and young adults. This study aimed to examine the relationship between elevated blood triglyceride levels and the incidence and severity of acne vulgaris in young adults. A cross-sectional design was utilized, involving 85 patients aged 17-25 years from a cosmetic clinic in Surabaya, Indonesia. Triglyceride levels were measured and classified into two categories: normal (less than 150 mg/dL) and high (more than 150 mg/dL). The severity of acne vulgaris was assessed using the Global Acne Grading System (GAGS). Statistical analysis using the chi-square test revealed a significant association between elevated triglyceride levels and the incidence of acne vulgaris (p = 0.03). However, no significant correlation was found between triglyceride levels and acne severity (p = 0.09). These findings suggest that while elevated triglyceride levels may increase the risk of developing acne vulgaris, other factors such as hormonal, genetic, and lifestyle elements may play a more prominent role in determining acne severity. Clinically, reducing triglyceride levels through dietary interventions or pharmacological therapies may serve as a preventive measure for acne vulgaris. Further research is required to explore the mechanisms underlying this relationship and the potential role of lipid management in acne treatment.